RESPONSE OF POTATO TO POTASSIUM FERTILIZER SOURCES AND APPLICATION METHODS IN ANDISOLS OF WEST JAVA - Nikardi Gunadi (Indonesian Journal of Agricultural Science, 2009)
An experiment to determine the response of potato to potassium (K) fertilizer sources and application methods in Andisols of West Java was conducted at a farmer’s field in the highland area of Pangalengan (1400 m asl.), West Java from August to November 2004. The treatments consisted of two K fertilizer sources (potassium chloride-KCl and potassium sulphate-K2SO4), two K rates (150 and 250 kg K2O ha-1), and three application methods (single, split, and split combined with foliar application), were arranged in a randomized complete block design with four replications. In the single application treatment, K was applied at planting, while in the split application treatment the K was applied half rate at planting and the rest at 6 weeks after planting (WAP). In the split combined with foliar application treatment, the K fertilizer was applied half rate at planting, a quarter rate at 6 WAP and another quarter rate by foliar spraying at 7, 8 and 9 WAP. The results showed that plant height was not significantly affected by the treatment (P >0.05). However, the sources and application methods of K fertilizer affected canopy cover, crop cover weeks (CCW), tuber dry weight (DW), and total plant DW at 10 WAP. Potatoes supplied with K2SO4 either in split or split combined with foliar application had significantly higher percent canopy cover, CCW, tuber DW, and total plant DW than those supplied with K fertilizer in single application. Potatoes supplied with K2SO4 had a higher tuber yield compared to those fertilized with KCl, especially under split or split combined with foliar application. To attain the same level of tuber yield as in the split combined with foliar application method, the rate of K2SO4 should be increased from 150 to 250 kg K2O ha-1 when using single application. It is therefore suggested that K2SO4 for potatoes should be used in split application combined with foliar application.